Availability and Challenges of Guidance and Counseling Services for Female Postgraduate Students at the University of Dar es Salaam - Rushahu, Bernadetha Gabriel (Papers in Education and Development, 2022)
Abstract The purpose of this study was to explore the availability and challenges of guidance and counselling services provided to female postgraduate students at the University of Dar es Salaam in Tanzania. The sample size was twenty-two participants consisting of 14 female postgraduate students, six counselors and two officials from the Dean of Student ' s office. Interviews, focus group discussions and observations were used to gather qualitative data. According to the findings, the majority of the female postgraduate students face numerous obstacles in achieving their educational goals. Thus, more awareness ought to be raised on how to access the available counselling services within the campus. Keywords: guidance, counseling, female postgraduate students